Extraordinary long detection window of a synthetic cannabinoid metabolite in human urine – Potential impact on therapeutic decisions. Issue 3 (4th February 2020) - Franz, Florian; Haschimi, Belal; King, Leslie A.; Auwärter, Volker
Abstract: Synthetic cannabinoids (SCs) have become established drugs of abuse. They play an increasing role in drug therapy, where abstinence control testing is required. Differentiation between recent drug uptake and uptake in the distant past is important for drug therapy. This study aimed to evaluate the detection window of a metabolite commonly used as a consumption marker for AB‐FUBINACA and AMB‐FUBINACA (synonym: FUB‐AMB) in urine analysis. The acidic hydrolysis metabolite was quantified in urine samples of a drug user by applying a validated analytical method. The concentration profile of the metabolite was correlated with usage data of the subject. Pharmacokinetic properties of AB‐FUBINACA were collected by analysis of serum and urine samples from a controlled administration study (single oral ingestion of AB‐FUBINACA). Thirteen urine samples were taken without advance notice over 2 years. The metabolite was detected in the first urine sample at 0.77 ng/mg creatinine and subsequently in concentrations ranging from 0.06 to 0.29 ng/mg creatinine. Usage data showed credible abstinence from SCs during this period. The pharmacokinetic properties observed within the controlled self‐administration study supported the hypothesis of distribution into deeper compartments and long‐lasting elimination (serum concentration–time curve showing biphasic kinetics). An elimination phase of over 1 year after the last drug uptake seems plausible in cases of extensive consumption. To avoid misinterpretation of positive findings, we recommend testing patients with known SC use at the beginning of the abstinence program and to re‐test continuously at short time intervals. These data enable the correct interpretation of analytical findings. Abstract : The study aimed at evaluating the detection window of a metabolite commonly used as a consumption marker for AB‐FUBINACA and AMB‐FUBINACA (synonym: FUB‐AMB) in urine analysis. The presented data enable correct interpretation of analytical findings.